Re-vegetation Improves Soil Quality by Decreasing Soil Conductivity and Altering Soil Microbial Communities: A Case Study of an Opencast Coal Mine in the Helan Mountains - Li, Zihao; Liu, Bingru; Chen, Zifeng; Mao, Dachuan; Jiang, Xingsheng (Frontiers in Microbiology, 2022)
Microbial communities constitute a diverse genetic resource pool in the soil and are key indicators of soil health and quality. How re-vegetation affects soil microbial diversity and community composition at the dump of an opencast coal mine is largely unknown. Using high-throughput sequencing, we performed a comparative study of the bacterial and fungal communities from non-vegetated (bare land) soil and from areas re-vegetated by Astragalus laxmannii, Halogeton arachnoideus, and Artemisia desertorum at an opencast coal mine in the Helan Mountains in western China. The results indicated that re-vegetation significantly reduced soil salinity. The soils re-vegetated by all three plant species showed higher bacterial species richness than the bare land, while only A. desertorum and A. laxmannii re-vegetated soils showed significantly higher fungal species richness compared with bare land. The bacterial and fungal β-diversity values were significantly different between vegetated and non-vegetated soils, while the differences were stronger regarding bacterial communities compared to fungal communities. Actinobacteria, Proteobacteria, Chloroflexi, and Bacteroidota were the main representative bacterial phyla, while Ascomycota and Basidiomycota were dominant in fungal communities. The relative abundance of Choroflexi was lower in the soil of re-vegetated land, while those of Proteobacteria and Bacteroidota were higher in A. laxmannii and A. desertorum re-vegetated soils. The decreasing soil conductivity that occurred with re-vegetation was found to be an important environmental determinant of the soil microbial community. This study provides evidence that re-vegetation may enhance soil quality via decreasing soil conductivity and altering the soil microbial community, and that compared to H. arachnoideus and A. desertorum, A. laxmannii can be a better choice of plant species for re-vegetation.